A Realistic Perspective to Transitional Justice - Mirza Satria Buana (Jember University Press, 2020)
Indonesia is one of the most democratized countries in Asia. There have been some improvements both in political and legal aspects; the most powerful legal reform was the amendments of the 1945 Constitution. In the context of civil and political rights, Indonesian people have exercised their constitutional rights to select political leaders, rotate elites and to enjoy greater civil liberty, even though there are still many rooms for improvements. One of the most vital hurdles is the failure of the reformed governments to settle gross-violation of human rights cases happened in the past. Suharto’s authoritarian regime had exercised repressive actions toward oppositions and civil society movements, including universities’ students, activists and minorities. The ad hoc Court of Human Rights had failed to reveal the truth for some prominent cases, let alone providing remedy and reconciliation. It was highly believed that the trials were conducted only as safeguards to prevent international intervention on Indonesia’s past unlawful violations.